2018
DOI: 10.1186/s12889-018-6069-2
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with social casino gaming among adolescents across game types

Abstract: BackgroundWith the proliferation of social casino games (SCGs) online, which offer the opportunity to gamble without monetary gains and losses, comes a growing concern regarding the effects of these unregulated games on public health, particularly among adolescents. However, given the limited research pertaining to SCG use, little is currently known about the manner in which adolescents engage with this new gambling medium. The present study aims to identify the factors that characterize adolescent social casi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 83 publications
3
27
2
Order By: Relevance
“…The prevalence of social casino spending may therefore be high. A recent large-scale survey of Canadian adolescents (n = 10,035) found that as many as 12.4% of respondents had recently played social casino games (Veselka et al, 2018). However, the generalisability of this figure to other populations is unclear.…”
Section: Social Casino Gamesmentioning
confidence: 99%
“…The prevalence of social casino spending may therefore be high. A recent large-scale survey of Canadian adolescents (n = 10,035) found that as many as 12.4% of respondents had recently played social casino games (Veselka et al, 2018). However, the generalisability of this figure to other populations is unclear.…”
Section: Social Casino Gamesmentioning
confidence: 99%
“…Links between social gambling and GD are not linear and different factors-individual and environmental factors or behavioral characteristics linked to gamblingmay influence gambling status and the development of the gambling behavior 1) . Problem gambling (PG) is more likely to occur among men [1][2][3]8) , with psychiatric disorders 8) , or individuals of extreme age [9][10][11][12] . Environmental factors, such as level of income, socio-economic integration, or social support and working status have an influence, both on PG prevalence worldwide and on an individual's gambling trajectory between social gambling and GD 1,4,8) .…”
Section: Introductionmentioning
confidence: 99%
“…A Canadian sample of youth in grades 9–12 found 12.4% had played SCGs in the past 3 months. These youth were more prevalently classified as experiencing problem gambling ( 18 ). A similar study in the United States found that ~10% of adolescent gamblers reported gambling at a casino, with estimates of 40% among those with gambling problems ( 42 ).…”
Section: Convergence Of Gambling and Videogamingmentioning
confidence: 99%
“…Limited or no age restrictions for online games such as free-to-play slot machines may allow youth early opportunities to engage in gambling-like activities that may lead to gambling problems ( 16 ). Social casino games (SCGs) that involve virtual currency may lead to monetary gambling ( 17 , 18 ). Other videogaming-related features such as loot boxes 1 ( 19 ) and skins betting 2 ( 20 ) offer non-monetary rewards with in-game value that may also have monetary value.…”
Section: Introductionmentioning
confidence: 99%